CLOUD STRUCTURE OF INTERSTELLAR MATTER. OBSERVATIONAL PARAMETERS - Gosachinskij, I. V.; Morozova, V. V. (Одеські астрономічні публікації, 2017)
Parameters of 7600 HI clouds were determined on the base of HI RATAN-600 Survey in the second and third quadrants of galactic longitudes. The spectra of cloud linear diameters, HI densities and masses are obtained first for such huge population of clouds. Mass spectrum of HI clouds shows that, in middle mass range, the process of coalescence in cloud{cloud collisions predominates, but the clouds with low masses are probably evaporated due to the very hot ISM component. It is found that mean clouds linear diameters along Galactic plane are 2.5 times greater than in transverse direction. The relation between HI concentrations and cloud diameters is obtained in the form of nH ∞d 1.25±0.01 probably regardless of selection effects. It is shown that velocity dispersion does not depend on cloud diameters, as distinct from molecular clouds. It is found that 16% of HI clouds have systematic velocity gradients across cloud disks that is may be due to clouds rotation. Mean clouds angular rotational velocity is about 5x10 -14s -1 and observable quantities of clouds with opposite directions of rotation are equal within 5% in both galactic quadrants investigated.